QUESTIONING THE RELEVANCE OF SOLUTION pH CALCULATION - André Fernando de Oliveira (The Journal of Engineering and Exact Sciences, 2020)
A brief discussion on the unnecessary calculation of pH in solution was done, as the historical reasons for this need before the invention of commercial pH meter was widely diffused. An alternative approach for acid-base equilibrium evaluation was proposed, without approximation or need of application only for simple solutions. The central aspect for the new approach is the determination of equilibrium concentration of all chemical species in solution, including the strong acid or base concentration for adjusting of pH of solutions. Therefore, the proposed method allowed the calculation in a mixture, including several polyprotic systems. Two detailed examples were presented. The effective electrical charge parameter was formally defined.